Risk factors of LEEP margin positivity and optimal length of cervical conization in cervical intraepithelial neoplasia - Cong, Qing; Yu, Yi; Xie, Yu; Li, Yanyun; Sui, Long (Frontiers in Oncology, 2023)
Background: The conization length for cervical precancerous lesion is essential for treatment but left undetermined. This study aims to explore the reasonable and optimal conization length in patients with different types of cervical transformation zones (TZ) to reach the treatment outcome of margin negative in the surgery. Methods: From July 2016 to September 2019, a multi-center prospective case control study with or suspicion of cervical precancer were enrolled from five medical centers in Shanghai, China. The clinical characteristics, cytology, HPV, histopathology, and details of cervical conization were recorded. Results: 618 women were enrolled in this study. 6.8% (42/618) had positive internal (endocervical and stromal) margins and 6.8% (42/618) had positive external (ectocervical) margins of LEEP specimen. Comparing positive internal margin group with negative group, age(P=0.006) and cytology (P=0.021) was significantly different. Multivariate logistic regression analysis showed the risk factors for positive internal margin were cytology ≥ HSIL (OR 3.82, P=0.002) and age (OR 1.11, P<0.001). Positive internal margin rate was 2.7%, 5.1% and 6.9% in TZ1, TZ2 and TZ3, while positive external margin was 6.7%, 3.4% and 1.4% in respective TZs. In TZ3 group, the HSIL positive internal margin of the 15-16mm group (10.0%, 19/191) was significantly greater than TZ1 (2.7%, 4/150) (P =0.010) and TZ2 (5.0%, 9/179) (P=0.092); when excision length increases to 17-25mm, the positive internal margin rate was dramatically decrease to 1.0% (1/98). Conclusion: Cervical excision length of 10-15mm is reasonable for TZ1 and TZ2 patients while 17-25mm is optimal for TZ3 excision with more negative internal margins.